On the limits of observing motion in time-resolved X-ray scattering - Ware, Matthew R. (Philos Trans A Math Phys Eng Sci, 2019)
Limits on the ability of time-resolved X-ray scattering (TRXS) to observe harmonic motion of amplitude, A and frequency, ω(0), about an equilibrium position, R(0), are considered. Experimental results from a TRXS experiment at the LINAC Coherent Light Source are compared to classical and quantum theories that demonstrate a fundamental limitation on the ability to observe the amplitude of motion. These comparisons demonstrate dual limits on the spatial resolution through Q(max) and the temporal resolution through ω(max) for observing the amplitude of motion. In the limit where ω(max) ≈ ω(0), the smallest observable amplitude of motion is A = 2π/Q(max). In the limit where ω(max)≥2ω(0), A≤2π/Q(max) is observable provided there are sufficient statistics. This article is part of the theme issue ‘Measurement of ultrafast electronic and structural dynamics with X-rays’.